Pemanfaatan Ampas Tahu Sebagai Bahan Baku Pembuatan Biodiesel - Trisnawati, Trisnawati; Walanda, Daud K.; Said, Irwan (Universitas Tadulako, 2016)
Biodiesel is an alternative raw material for fuel of diesel motor made from vegetable oil. This study attempted to utilize tofu dregs as raw material for biodiesel. This study aimed to determine the yield of biodiesel produced and the content of methyl esters in the biodiesel yield, and to analyze the quality of biodiesel produced based on Indonesian national standard (SNI). This study consisted of four stages: the provision of samples, pre-treatment, esterification and transesterification, and analysis of the quality of biodiesel produced which include the density at 15 °C, the viscosity at 40 °C, and the moisture content. The results showed that the yield of biodiesel was 4.01%, and the content of methyl ester shown by larger Rf (0.87) using eluent of hexane:diethylether:formic acid. Results of the analysis of biodiesel quality obtained the density at 15°C was 864 kg/m3, the viscosity at 40 °C was 2.57 mm2/s, and the water content was 4%. Based on the parameters ofthe density at 15 °C and the viscosity at 40 °C, the product of biodiesel met the requirements of SNI, while in term of the water content the product did not meet the requirements of SNI.